Dynamic sulfur and carbon cycles related to microbial sulfate reduction and volcanic activity during the Hirnantian glaciation in the Upper Yangtze Basin, South China - Dong, Zaitian; Wang, Zetang; Zhang, Wenli; Zhao, Fei; Du, Yunhang; Zhu, Yuxuan; Fu, Xuehai; Wang, Chaoyong (Frontiers in Earth Science, 2022)
Parallel positive excursions of organic carbon (δ13Corg) and pyrite sulfur (δ34Spy) isotopes occurred globally during the Hirnantian glacial period. However, the reasons for these isotope excursions and their relationship with paleoenvironmental dynamics are not fully understood. This study presents a high-resolution geochemical investigation of the Tianlin section of the Upper Yangtze Basin, South China. The total organic carbon (TOC), iron speciation, trace elements, δ13Corg, and δ34Spy were analyzed and compared with published results from the other four sections in the same basin. A negative relationship was observed for the sulfate reduction index (SRI) with TOC and organic carbon accumulation rate. This suggests that the activity of sedimentary organic matter was not the main factor inhibiting microbial sulfate reduction (MSR). The significant positive correlations of SRI with pyrite and δ34Spy showed that MSR promoted the formation of pyrite and that the availability of sulfate was the main limiting factor for the δ34Spy change. The negative excursions of δ13Corg and δ34Spy during the pre-glacial and post-glacial periods were coupled with dense segments of bentonite, indicating that volcanism was the main driving force for the negative excursions of C and S isotopes. Moreover, the sulfate input of rivers, restored at the post-glacial period, was the main reason for the continued negative excursion of S isotopes. Our results emphasize the key role of MSR and volcanic activity in C and S isotope excursions and their corresponding environmental changes in semi-restricted basins during the Hirnantian glaciation.